Correlating Macro and Atomic Structure with Elastic Properties and Ionic Transport of Glassy Li2S‐P2S5 (LPS) Solid Electrolyte for Solid‐State Li Metal Batteries. Issue 19 (1st April 2020) - Garcia‐Mendez, Regina; Smith, Jeffrey G.; Neuefeind, Joerg C.; Siegel, Donald J.; Sakamoto, Jeff
Abstract: A combination of high ionic conductivity and facile processing suggest that sulfide‐based materials are promising solid electrolytes that have the potential to enable Li metal batteries. Although the Li2 S‐P2 S5 (LPS) family of compounds exhibit desirable characteristics, it is known that Li metal preferentially propagates through microstructural defects, such as particle boundaries and/or pores. Herein, it is demonstrated that a near theoretical density (98% relative density) LPS 75‐25 glassy electrolyte exhibiting high ionic conductivity can be achieved by optimizing the molding pressure and temperature. The optimal molding pressure reduces porosity and particle boundaries while preserving the preferred amorphous structure. Moreover, molecular rearrangements and favorable Li coordination environments for conduction are attained. Consequently, the Young's Modulus approximately doubles (30 GPa) and the ionic conductivity increases by a factor of five (1.1 mS cm −1 ) compared to conventional room temperature molding conditions. It is believed that this study can provide mechanistic insight into processing‐structure‐property relationships that can be used as a guide to tune microstructural defects/properties that have been identified to have an effect on the maximum charging current that a solid electrolyte can withstand during cycling without short‐circuiting. Abstract : It is demonstrated that Li2 S‐P2 S5 75‐25 can be densified close to its theoretical density, while preserving the preferred amorphous phase optimizing the hot‐pressing temperature and pressure. Molecular rearrangements and favorable Li coordination environments for conduction are attained. Consequently, the Young's Modulus is approximately doubled and the ionic conductivity is increased by a factor of five compared to conventional room temperature molding conditions.